Letramento funcional em saúde bucal e qualidade de vida em gestantes: um estudo transversal - Oliveira, Gabriella Mendes de (2020)
INTRODUCTION: Functional health literacy is the ability of an individual to gain accessto and understand and use information in a way that promotes and maintains good health and seems to be fundamental for improving the perception of quality of life. OBJECTIVE: To identify the level of functional health literacy of pregnant women attended at a public university hospital and its comparison with the quality of life of these women. METHODOLOGY: Cross-sectional study with 326 pregnant women who responded to Breald-30 and WHOQOL (bref). RESULTS: Most pregnant women (80%) had a high degree of functional literacy, which was associated with education (r = 0.3; p <0.001), income (r = 0.4; p <0.001) and the WHOQOL- BREF (r = 0.3; p <0.001). Low literacy pregnant women had a worse quality of life in the environmental domain compared to high literacy pregnant women (p = 0.001; Cliff delta = 0.335). CONCLUSION: Pregnant women with a worse degree of functional literacy have a worse perception of quality of life in the environmental domain. Oral health literacy must be considered in health practices, as it can facilitate access to health services, adherence to health recommendations among pregnant women and, consequently, in improvements in the perception of quality of life.